Downlink hierarchical scheduling method for relay-enhanced cellular network based on TG-PF - Hua QU; Ya-lan SONG; Ji-hong ZHAO; Yi-wei LI (Tongxin xuebao)
Hierarchical scheduling model for relay-enhanced cellular network was designed to divide the w e process of resource scheduling in relay-enhanced cell into two parts,which are high-level scheduling accomplished by eNode B and low-level scheduling accomplished by Relay Node.Based on this,a throughput guaranteed proportional fair (TG-PF) scheduling algorithm was also proposed.The algorithm fully takes the advantages of Max C/I algorithm and PF algorithm consideration,so that it can effectively improve cell lay-enhanced cellular network based on TG-PF,PF algorithm and TG-PF algorithm are separately used in high-level and low-level scheduling process to satisfy the system throughput and scheduling fairness requirements of relay-enhanced cell.Simulation results suggest that the proposed method can tremendously improve cell edge throughput with a small size sa-crifice in scheduling fairness.